Due Process in Medical Education: Legal Considerations. (13th November 2018) - Conran, Richard M.; Elzie, Carrie A.; Knollmann-Ritschel, Barbara E.; Domen, Ronald E.; Powell, Suzanne Zein-Eldin
Throughout the medical education continuum, some students encounter difficulty in meeting academic or professional standards that leads to remediation or dismissal. Termination of a student without due process may lead to litigation by deprivation of a student's property or liberty interest. This article outlines the concept of procedural and substantive due process as applied to litigated student dismissal cases in undergraduate and graduate medical education. Determination of the amount of due process owed is based on whether the dismissal is academic or nonacademic. The decision to dismiss a student where the entire student record has been reviewed, due process provided, and the institution complied with its own policies is usually upheld by the courts in litigation.